High Prevalence of Carbapenem‐resistant Enterobacteriaceae in Bangladesh: A Systematic Review and Pooled Analysis - Begum , Khadija; Rahman , Kaniz; Yeasmin , Fouzia; Shahid , Mohammad Moin; Alam, Md Morshad (Bangladesh Journal of Medicine, 2026)
Background: Carbapenem-resistant Enterobacteriaceae (CRE) poses a public-health threat due to limited treatment options thus leading to substantial morbidity and mortality. We aimed to systematically review the prevalence of CRE in Bangladesh from previously published literatures with organism distribution and associated resistance genes. Methods: Following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, we searched PubMed, Google Scholar, and the Directory of Open Access Journals (DOAJ) to identify cross-sectional studies from Bangladesh. After screening and eligibility assessment, we identified seven studies that met the inclusion criteria. Results: The crude prevalence of CRE was 11.79% (95% CI, 10.64–13.05). The pooled prevalence was 15.46% (95% CI, 6.85–31.27; I² = 93.1%), indicating high between-study heterogeneity. Predominant species were Escherichia coli (40.57%), Klebsiella pneumoniae (25.47%), and Enterobacter cloacae (3.77%); Enterobacter spp. (15.99%) and Klebsiella spp. (4.72%) were also frequent. Among resistance genes, the NDM family predominated: blaNDM-5 was detected in 30 isolates and blaNDM-1 in 29. Other reported genes included blaOXA-1 (n = 17) and blaCTX-M-1 (n = 10). Conclusion: It’s urgent to strengthen the national antimicrobial resistance surveillance and establishment of antimicrobial-stewardship programs. Further research should investigate the transmission dynamics and genetic contexts of resistance determinants within these bacterial lineages. Bangladesh J Medicine 2026; 37(2): 92-99